Ejecución presupuestaria del periodo 2021 y 2022 en el Gobierno Autónomo Descentralizado de la parroquia La Unión. - Alcívar Arias, Odalis Nicole (2023)
In the context of the Autonomous Decentralized Municipal Government (GAD) of Baba town, there is a need to assess the discrepancy between planned budgets and actual execution, considering the gap caused by factors such as the economic crisis and variations in resource availability, leading to significant consequences such as insufficient funds for projects, delays or cancellation of works, and inefficient use of public resources. This study is justified by the importance of ensuring that public resources are allocated and used effectively for local development and community well-being. The objective is to determine the budget execution of the GAD of La Unión parish during the periods 2021-2022. To achieve this, a methodological approach combining the analysis of budget schedules provided by the GAD with an interview with the chief financial officer is employed. It is concluded that current and capital revenues experienced executions close to 91.43% and 93.68% in 2021, reaching 100% in 2022. Current expenditures were prioritized over capital expenditures. Furthermore, it was identified that the most affected budget item due to budget reduction was public works, highlighting the need for improvement in planning and execution in this regard.